Eﬀectiveness of dry needling combined with eccentric strength training in lateral epicondylalgia with trigger points - Shanmugam, Sukumar; Mathias, Lawrence; Muthukrishnan, Ramprasad; Kumar Kandakurthi, Praveen; Durairaj, Satheeskumar (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Lateral epicondylalgia (LE) is commonly presented with myofascial trigger points (MTrPs) among adults. Dry needling (DN) is used less frequently as a ﬁrst-line treatment in LE with trigger points, and the short and long-term eﬀectiveness of DN in these populations were not studied. Hence, this study compared the eﬀectiveness of DN with conventional physio-therapy in the population of LE with myofascial trigger points.Methods. For four weeks, the experimental group (n = 19) received DN with weekly one session, and the control group (n = 19) received therapeutic ultrasound combined with deep friction massage for 2 sessions per week at the active sites of active MTrPs. Both groups performed two eccentric exercises sessions from the 5th to the 6th week. Handgrip, pain and disability scores of patient rated tennis elbow evaluation (PRTEE) at baseline, 4th week, 6th week, and follow-up of 12th week were analysed.Results. Handgrip strength, pain, and disability scores were signiﬁcantly improved for the experimental group at 4th week (SMD of 1.21 kg in handgrip, 12.26 in PRTEE scores) and 6th week (SMD of 1.58 kg in handgrip, 10.15 in PRTEE scores) compared to the control group. However, no signiﬁcant group diﬀerences (p > 0.05) after 12th week either grip strength (SMD = 0.84) or PRTEE scores (SMD = 3.74) were obtained.Conclusions. Dry needling with exercise produced greater short-term improvements in grip strength and disability compared to the control group. However, no signiﬁcant diﬀerence in outcomes was found between groups over a 12-week follow-up period.
Keywords: orthopedics; physical activity and sports of handicapped; sport physiotherapy